A Cognitonics Approach to Computer Supported Learning in the Mexican State of Oaxaca (Informatica, 2014)
Cognitonics is a new science which looks at ways to reconcile human socio-spiritual development with increasingly rapid human intellectual development in the new context of technological advances and increased cultural homogeny. This is particularly relevant in areas such as education and informatics where children are found to be increasingly capable to control and adapt to new technological advances yet often suffer from a lack of social development or are unable to engage with aspects of their own cultural heritage. In this study we consider the application of a cognitonics based approach to the problems of the Oaxacan education system, particularly for indigenous children who suffer from a loss of culture and diminished provision of education due to a lack of resources and regular teacher strikes. Specifically, we look at how the introduction of face-to-face collaborative video games can help develop academic, information-technology and social skills together while promoting spiritual well-being and cultural identity.